2014
DOI: 10.3389/fphys.2014.00368
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of signal amplification by macromolecular assemblies for the control of chromosome segregation

Abstract: The control of chromosome segregation relies on the spindle assembly checkpoint (SAC), a complex regulatory system that ensures the high fidelity of chromosome segregation in higher organisms by delaying the onset of anaphase until each chromosome is properly bi-oriented on the mitotic spindle. Central to this process is the establishment of multiple yet specific protein-protein interactions in a narrow time-space window. Here we discuss the highly dynamic nature of multi-protein complexes that control chromos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 144 publications
(201 reference statements)
0
3
0
Order By: Relevance
“…The kinetochore not only provides this physical linkage but is also endowed with spring-like properties that enable it to respond to tension that through the spindle assembly checkpoint (SAC) can signal and correct improper MT attachments. It also acts as a platform for the loading of the SAC proteins and of motor and other MT-associated proteins that regulate behaviour of the MT plus ends and chromosome movement (reviewed in [2][3][4][5]). To fully understand these multiple properties, it is necessary to obtain precise structural information of how the kinetochore is built.…”
Section: Introductionmentioning
confidence: 99%
“…The kinetochore not only provides this physical linkage but is also endowed with spring-like properties that enable it to respond to tension that through the spindle assembly checkpoint (SAC) can signal and correct improper MT attachments. It also acts as a platform for the loading of the SAC proteins and of motor and other MT-associated proteins that regulate behaviour of the MT plus ends and chromosome movement (reviewed in [2][3][4][5]). To fully understand these multiple properties, it is necessary to obtain precise structural information of how the kinetochore is built.…”
Section: Introductionmentioning
confidence: 99%
“…An additional layer of complexity in SAC regulation is represented by the extent of post-translational modifications of SAC components, including BubR1, in which phosphorylation, acetylation and ubiquitylation affect the stability, reversibility, subcellular localisation, turnover, and hierarchical order of assembly/disassembly of SAC subcomplexes [47][48][49]. For instance, in prometaphase, BubR1 is acetylated by the histone acetyltransferase P300/CBP-associated factor (PCAF) at residue K250, a modification that protects BubR1 from degradation by APC/C-Cdc20 [50,51].…”
Section: The Importance Of Post-translational Modificationsmentioning
confidence: 99%
“…Multiple studies indicate that tumors are particularly dependent on redox-regulating pathways and that this vulnerability can be exploited by targeted therapeutics (18,19). In recent years, several kinases have been identified that regulate the sensitivity of cancer cells to paclitaxel by inhibiting centrosome splitting (20) or enhancing microtubule stability (21,22). Much less attention has been given to kinases that affect paclitaxel sensitivity by modulating cancer cell metabolism.…”
Section: Introductionmentioning
confidence: 99%